Jonas Mekas : Interviews - Smulewicz-Zucker, Gregory R., 1983- (Book collections on Project MUSE., 2020)
"Collected interviews with the director of avant-garde films such as Walden (Diaries, Notes, and Sketches); Reminiscences of a Journey to Lithuania; and As I Was Moving Ahead Occasionally I Saw Brief Glimpses of Beauty"--